Model Pembelajaran Kooperatif Dalam Meningkatkan Minat Belajar Pendidikan Agama Kristen - Pingga, Yulia Susanti (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2021)
This research intends to examine the use of cooperative learning models in Christian Religious Education (PAK) subjects to increase the learning interest of students of class XI IPS 3 SMAN 1 Kupang. This research uses qualitative descriptive methods. Informants are 26 students and 1 PAK teacher. The results revealed that there was a positive response from learners when learning in the classroom was conveyed using the cooperative learning model. This is indicated by indicators: students feel comfortable and happy to follow learning using the cooperative learning model, there is attention from students when the subject matter is delivered using the cooperative learning model as a support to motivate students to be interested in learning activities, students are so interested in following learning by using the cooperative learning model because they get assignments and opportunities to become leaders (leaders) for students. Friends in the group, students are able to remember the material that has been delivered through the cooperative learning model because in group learning they help each other find the material discussed, students can understand the subject matter delivered through the cooperative learning model, as well as the growing interest in learning students when learning materials are delivered using the cooperative learning model. Penelitian ini bermaksud untuk meneliti penggunaan model cooperative learning pada mata pelajaran Pendidikan Agama Kristen (PAK) untuk meningkatkan minat belajar siswa kelas XI IPS 3 SMAN 1 Kupang. Penelitian ini menggunakan metode deskriptif kualitatif. Informan yaitu 26 orang siswa-siswi dan 1 orang guru PAK. Hasil penelitian mengungkapkan bahwa terdapat respon positif dari peserta didik saat pembelajaran di kelas yang di sampaikan dengan menggunakan model cooperative learning. Hal ini ditunjukkan dengan indikator: siswa merasa nyaman dan senang mengikuti pembelajaran dengan menggunakan model cooperative learning, adanya perhatian dari siswa ketika materi pelajaran disampaikan menggunakan model cooperative learning sebagai pendukung untuk memotivasi siswa agar berminat dalam kegiatan pembelajaran, siswa begitu tertarik mengikuti pembelajaran dengan menggunakan model cooperative learning karena mereka mendapat tugas dan kesempatan untuk menjadi ketua (pemimpin) bagi teman-teman dalam kelompok, siswa mampu mengingat materi yang telah disampaikan melalui model cooperative learning karena dalam pembelajaran kelompok mereka saling membantu menemukan materi yang dibahas, siswa dapat memahami materi pelajaran yang disampaikan melalui model cooperative learning, serta bertumbuhnya minat belajar siswa ketika materi pembelajaran disampaikan menggunakan model cooperative learning.